2009
DOI: 10.1152/ajpregu.90959.2008
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training from late middle age until senescence does not attenuate the declines in skeletal muscle aerobic function

Abstract: We previously showed that 7 wk of treadmill exercise training in late-middle-aged rats can reverse the modest reductions in skeletal muscle aerobic function and enzyme activity relative to values in young adult rats (Exp Physiol 93: 863-871, 2008). The purpose of the present study was to determine whether extending this training program into senescence would attenuate the accelerated decline in the muscle aerobic machinery normally seen at this advanced age. For this purpose, 29-mo-old Fisher 344 Brown-Norway … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 63 publications
4
38
0
Order By: Relevance
“…However, there is also evidence that the plasticity of the NMJ to physical activity is attenuated with ageing and denervation may become exacerbated by exercise training in very old age 7. Specifically, aged rats subjected to long‐term exercise training exhibited greater muscle atrophy and myocyte oxidative damage compared with aged‐matched sedentary controls 295, 296. The potential for physical activity to induce adverse effects when initiated in old age has not been addressed in humans.…”
Section: Non‐enzymatic Key Antioxidants That Contribute To the Maintementioning
confidence: 99%
“…However, there is also evidence that the plasticity of the NMJ to physical activity is attenuated with ageing and denervation may become exacerbated by exercise training in very old age 7. Specifically, aged rats subjected to long‐term exercise training exhibited greater muscle atrophy and myocyte oxidative damage compared with aged‐matched sedentary controls 295, 296. The potential for physical activity to induce adverse effects when initiated in old age has not been addressed in humans.…”
Section: Non‐enzymatic Key Antioxidants That Contribute To the Maintementioning
confidence: 99%
“…In any case, recent advances imply that a modulation of PGC-1 ␣ levels in muscle might be beneficial for sarcopenia patients. First, old rats with a blunted induction of PGC-1 ␣ expression subsequent to exercise are also resistant to exercise-mediated improvement of sarcopenia [54] . Similarly, PGC-1 ␣ is required for exercise-mediated prevention of the functional decline of mitochondrial enzymes in aging in mice [ 60 ].…”
Section: Therapeutic Potentialmentioning
confidence: 99%
“…The training protocol is described in detail in a previous publication from our laboratory (3). Briefly, the rats were trained on a treadmill as described in our previous study (2) over the first 2 mo (60 min, 5 days/wk), as this was shown to yield significant benefits for skeletal muscle and whole body function in late-middle-aged animals.…”
Section: Animalsmentioning
confidence: 99%